KAJIAN PENYESUAIAN TARIF RETRIBUSI BIDANG PERHUBUNGAN DI KABUPATEN BREBES - Waskita, Jaka; ., Gunistiyo; Faqihudin, M; ., Siswanto (PERMANA, 2012)
The purpose of this study is to examine the transportation sector levy rates in the Brebes District to be held adjustment, adjustment propose an alternative way of determining the transportation sector retribution rates based approach in line with the principles of economics, especially pricing of public services in order to reach all aspects: (i) the adequacy of revenues; (ii) the aspect of justice, (iii) economic efficiency, (iv) adininistrasi and political aspects, and (v) suitability as a source of local revenue. Way in which to determine the unit rates for each service users in accordance with the above criteria, based on consideration of: (i) estimate the economic capacity of the community, (ii) retribution rates other areas around it, (iii) to change based on inflation rates occurred in the area of ââBrebes district. Analysts levy rate adjustment is based on the assumption of using average inflation rate from 2003 to 2008 (5 years) is 8.94% per year. Keywords: Retribution, tariff adjustment, increase local revenue